1989
DOI: 10.1002/hep.1840100519
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic liver transplantation and the cytosolic estrogen-androgen receptor status of the liver: The influence of the sex of the donor

Abstract: Mammalian liver is known to contain cytosolic receptors for both estrogens and androgens. Furthermore, certain mammalian hepatic functions are known to display a sexual dimorphism. However, in clinical liver transplantation, the sex of the donor is not taken into consideration in selection of the donor. In this study, the effect of liver transplantation on the estrogen and androgen receptor content of the liver was determined. Adult male and female rats were subjected to orthotopic liver transplantation, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…31 A previous study in rats demonstrated that female-to-male liver transplantation significantly reduced the cytosolic estrogen receptors in grafts to the level of male liver within 10 days, whereas male-to-male liver transplantation maintain the estrogen receptor content. 9 Abrupt defeminization of female livers by reduction of estrogen receptor activity and exposure to the male hormonal milieu can impair mechanisms of protection of grafts from female donors.…”
Section: Discussionmentioning
confidence: 99%
“…31 A previous study in rats demonstrated that female-to-male liver transplantation significantly reduced the cytosolic estrogen receptors in grafts to the level of male liver within 10 days, whereas male-to-male liver transplantation maintain the estrogen receptor content. 9 Abrupt defeminization of female livers by reduction of estrogen receptor activity and exposure to the male hormonal milieu can impair mechanisms of protection of grafts from female donors.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have indicated that gender mismatch has an impact on graft failure, specifically in male recipients receiving grafts from female donors in adult deceased donor LT and adult LDLT . Although the poor graft prognosis was thought to result from reduced serum estrogen levels in male recipients and a lower number of estrogen receptors in male recipients of grafts from female donors , further long‐term study is warranted to clarify how hormonal factors affect the outcome of LT. In contrast, Nijagal et al .…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, one of the responses of the liver to exogenously administered estrogen is to enhance its synthesis of various transport proteins including sex-steroid-binding globulin (2) and thyroxine-binding globulin (12). In addition, the presence of specific estrogen-binding proteins within the liver, which presumably protect male hepatocytes from the unwanted effects of estrogen, have been identified and characterized in the liver (4). The amount of these proteins in the hepatic cytosol after puberty differ markedly between males and females (6).…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, transplantation of organs from adult donors of one sex (male or female) to a recipient of the opposite sex results in the finding of cytosolic estrogen and androgen receptor activity similar to those found in female liver (4). These changes in the sex hormone-receptor expression of the liver have been postulated to account for the unfavorable outcome associated with transplantation of organs harvested from females that are subsequently transplanted into adult males (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation